Kajian Biaya Penanganan Petikemas Melalui Terminal Petikemas Tanjung Priok - Yuliani, Apri (Warta Penelitian Perhubungan, 2011)
The tremendeous intensity of export/import activity using containers in Indonesia should be an opportunity to support economic development and improve public's welfare. In fact, it was hampered by the high logistics costs. This phenomenon's correctly proven by a periodic national logistics performance survey conducted by The World Bank, Logistics Performance Index (LPI). In 2010, World Bank ranked Indonesia in position 75 out of 155 countries, which is one of these performance considerations is the cost of shipping, that has put Indonesia at rank 80. Referring to the ESCAP model port tariff structure, the port tariff structure of Tg. Priok's divided into four sections. They are navigation, berth, cargo operations and other business. Compared to Port of Melbourne's tariff, Pelabuhan Tg. Priok even regulates a lower rate of tariff Based on interviews and observations, the detenninant factors causing high cost of logistics are: (i) illegal fees, mostly caused by inadequacy of infrastructure, red-tape bureaucracy, insufficient and less-regulated standard operating procedures, the absence of rotation mechanism and exclusive authority without supervision; (ii) the surcharge; and (iii) induced cost of unpredictability delivery process.Keywords : Handling costs, Tariff, Container